HUBUNGAN PERSEPSI PEKERJA, KETERSEDIAAN DAN TATA LETAK SAFETY SIGN DENGAN KEPATUHAN PEKERJA (Studi kasus Pada Pekerja di Gudang Finished Goods PT Indofood CBP Sukses Makmur Tbk Semarang) - Adhiatma Setiawan Nugroho; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat, 2019)
Safety sign is a risk hazard control that is administrative. Safety sign consists of safety information that must be understood by everyone who enters the work environment.The activity of lifting work in Finished Goods Warehouse has the potential to cause work accidents. The purpose of this study was to analyze the factor of the perception of employee, availability of infrastructure facilities, and placement of safety sign that iscorrelated with the workers in Finished Goods Warehouse. The dependent variable of this study was the compliance of workers. Meanwhile, the independent variables were the perception of employee, availability of infrastructure facilities, and placement of safety sign . This research was included as observational analytic study with a cross sectional study approach. The instruments of this study were questionnaires, and observation sheets. The sample of the study was 40 workers using the total sampling method.Based on the results of the Chi-Square statistical test, it isshowed that there was a correlation between the perception of workers(p-value = 0,018; α = 0.05), and the placement of safety sign (p-value = 0,006; α = 0.05) with the complianceof employee. However, there was no correlation between the availability of infrastructure (α = 0.05) withsafety sign . PT. Indofood CBP Sukses Makmur Tbk. Semarang Division Noodle is suggested to review the correct usage of language on safety sign s and use luminous materials in making safety sign . The writer advised the workers to obey and comprehend the existence of a safety sign in order to work safely.